PENGGUNAAN APLIKASI PEMBELAJARAN SELAMA PANDEMI PADA ANAK USIA DINI DI KECAMATAN BUBUTAN SURABAYA - Maria Qori’ah; Siti Masitoh; Sri Setyowati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This research is based on the government’s policy that learning must be carried out online due to the Covid-19 pandemic. The purpose of this research is to find out what applications have been used by teachers in Bubutan, Surabaya City during the Covid-19 pandemic to support online learning in early childhood education. The research method used is descriptive qualitative. Data collection was obtained from the results of a survey conducted by google form and interviews by WhatsApp. The results showed that there were many kinds of online learning support applications during the Covid-19 pandemic such as WhatsApp, zoom, google meet, google classroom, and pear deck. Whatsapp is the most widely used application and Peardeck is an application that is still unfamiliar to be used in the Bubutan, Surabaya City.